THE THREE MEANINGS OF TRUTH IN RELIGION - Mercier, Sean L (Journal of Dharma, 1996)
Most religionists vigorously hold that they possess the truth. In contrast the philosophers’ claim has usually been less pretentious. They prefer to describe their undertaking as a painstaking search for the truth. It has been said that the philosophers who once shared the pulpit with theologians have vacated it, leaving the theologians alone to preach the truth whereas they themselves assume now the humbler task of dealing with meanings than with truth •. Scientists too do not pretend to expose the plain truth about reality. The search for verisimilitude in science - l.e., "approximation .to the truth" - is a clearer and more realistic aim than the search for truth.! By and large philosophers and scientists have the wisdom to recognise the limits of their field.